Pemulihan Ekonomi Paska Konflik 1999 di Timor Leste: Peran Sektor Pertanian dalam Mengurangi Resiko Kekerasan dan Konflik - , Karlina Diah Indrias ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This thesis analyzed the influence of agriculture sectorâs development after 1999 conflict to violence and conflict risk in Timor Leste. By using qualitative research method based on reliable data sources, it is based on main argument that poverty and unemployment are the main catalysts of the increasing number of violent gangs and groups in Timor Leste that are often engaged in violent acts and conflicts. Therefore, related to the process of achieving the main goal of post conflict peacebuilding, the reduced level of violence and conflict are used as the main indicators. It shows that economy in post conflict peacebuilding should get significant portion since it is vital to tackle poverty and reduce unemployment. Since most of the people in Timor Leste work in agriculture field, the agriculture sector is one of the main sectors in Timor Lesteâs economy besides oil and gas sector. In the first chapter, the thesis critically reviewed the process of post conflict peacebuilding in Timor Leste and the strategic role of agriculture during the whole process knowing that most of Timor Leste people work in field. Based on the data, around 70% of the total working populations are farmers. It confirms the vital and strategic position of the agriculture sector. In the second chapter, the thesis reviewed the level of poverty and number of unemployment in Timor Leste after 1999 conflict and how they directly affect the level of violence and conflict risk. In the last chapter, the thesis reviewed the governmentâ and foreign institutionsâ role in developing agriculture sector after 1999 conflict while figuring out whatâs lack from them and how it affects the development process. Although officially Timor Leste government has considered agriculture sector one of several main priorities during post conflict peacebuilding but the results arenât satisfying yet. The growing number of gangs or groups, number of violent acts and conflict indicates that more efforts to develop agriculture need to be done. Besides, foreign institutions involved in post conflict peacebuilding still lack causing uneven aid distribution and program.